Measurements of multidimensional poverty and inequality in Malaysia - Mohamed, Zunika (2013)
Malaysia has become one of the role models for economic development, particularly in achieving remarkable economic growth and handling distributional issues related to addressing poverty, income inequality and the regional gap. Of late, the country is facing a middle income trap while having unsatisfied performance in certain areas such as crime, corruption, education and income distribution that imposed challenges for the country’s aim towards achieving a developed nation status by 2020. The inclusive development framework was introduced in 2010 with the objective to ensure equitable access to economic participation among all Malaysians. The current measurements of poverty and inequality which are based on income alone within the inclusive development framework are argued as inadequate, neither from theoretical nor the practical perspectives. Thus, this study attempts to propose a suitable measurement tools that can be used for evaluation and monitoring in a cohesive way. Specifically, the aims of this study are threefold. First, this study attempt to develop a Multidimensional Index of Poverty (MPI) for Malaysia by applying a multidimensional framework based on the “capability and functionings” approach developed by Sen (1976). Second, this study will develop a Multidimensional Index of Inequality (MII) in analyzing the various socio-economic disparities in Malaysia. Third, this study examines stability and consistency issues with respect to the proposed measurements of multidimensional poverty and inequality. The consistencies of the measures are critical to ensure that the measures proposed are technically sound enough to meet the objectives set forth. The measurement of multidimensional poverty among households in Malaysia is based on method by Alkire and Foster (2007 and 2011) for five dimensions of wellbeing, with two indicators each. These dimensions are finance, education, health, standard of living and environment. The multidimensional index of inequality for Malaysia is constructed by utilizing method developed by Decancq and Lugo (2009). Data from the Household Income Survey and Basic Amenities Survey (HISBA) for 2009 is used for these purposes. The stability and consistency checks on the two proposed indices of poverty and inequality are undertaken by checking for sensitivity and consistency in rankings of the indices under different scenarios, which include testing different weights and correlations using the same dataset as well as testing the same parameters using different dataset. Data from the HISBA for the year 2009, 2004 and the eKasih database are used here. Results from the construction of the MPI and MII for the year 2009 provide additional insight into poverty and inequality phenomena in Malaysia. The MPI calculation uncovers that the contribution of income to poverty in Malaysia is only marginal, with income contribute about 3.5 per cent. The households are actually deprived more in the standard of living, health, education and environment. Most importantly, the magnitude of the contribution of the dimensions differs when the households are evaluated according to sub-groups such as strata and ethnic groups. Consistent with the existing literature on regional economic progress, the standard of living deprivation is more prominent in the rural areas, as well as in the regions of Sabah and Sarawak. Notwithstanding that, heads of households’ educational achievement under education dimension single outs as fairly equal among the strata and region. Overall, the MII for Malaysia in 2009 is lower than the standard Gini income index to measure inequality, at 0.28 as compared to 0.44, respectively. Regional disparity also favors Peninsular Malaysia. Disparity in the rural areas continues to be higher than that of the urban area. It is striking to find that while the ethnic inequality under the standard income measure (Gini) shows a converging trend, the inequality among Bumiputera is higher compared to two other main groups of Chinese and India under the multidimensional framework. The two indices of MPI and MII that are proposed under this study are stable and consistent under various conditions tested. In short, consistent rankings of MPI and MII are produced when different weighting systems and parameters are used. Additionally, the methods that are employed are also stable when different datasets are used. This study concludes that the MPI and MII constructed under the multidimensional framework are suitable tools to supplement other standard measures of wellbeing in Malaysia. We propose that policy makers take into consideration the insights from these multidimensional phenomena in the endeavor to achieve inclusive growth in Malaysia. The decomposition of poverty by dimensions and by sub-groups can help in identifying resources allocation efficiently. This study makes significant contributions to the study of poverty and inequality in two ways. First, it proposes new measurement tools under the multidimensional framework that are suited for the need of middle-income country like Malaysia. This study shows that poverty in Malaysia is not just about income. The policy implication from this finding is that focus should be shifted to non-income dimensions such as the standard of living, education and health, to improve the wellbeing of the population. The results from the in-depth decomposition of poverty by spatial and groups suggested that identification of target groups for policy intervention has to take a different approach, beyond strata, region and main ethnic groups. In this case, efforts to improve capabilities of households should be set from the perspective of outcome-based and not just on output produced. Second, the analysis undertaken for the case of Malaysia added to growing literature on multidimensional poverty and inequality. The main limitation of this study is the unavailability of suitable data from similar sources. Thus, the scope of study is limited to five dimensions with a total of ten indicators.